EFFECTS OF FLY ASH CONTAMINATION ON THE ELECTRICAL PROPERTIES OF CERAMIC INSULATOR SURFACES - Moh. Rafli A. Bolilio; Lanto Mohamad Kamil Amali; Yasin Mohamad (Universitas Tarumanagara, 2025)
The decrease in insulator performance due to environmental pollution, especially by fly ash produced from Steam Power Plants (PLTU). Fly ash contains conductive elements that have the potential to reduce the surface resistivity of insulators, so that it can accelerate insulation failure, especially in humid or wet conditions. Therefore, it is important to study in depth the effect of fly ash on the electrical parameters of insulators, such as surface conductivity and breakdown voltage. The main objective of this study was to determine how much impact the content of conductive elements in fly ash has on the decrease in surface resistivity of insulators. The methods used include analysis of chemical elements in fly ash, simulation of variations in pollutant solution concentration, and testing of leakage current and breakdown voltage in an AC high voltage laboratory. The results showed that fly ash from PLTU Anggrek contains conductive elements of Iron (Fe) of 1.595%, Magnesium (Mg) 0.44%, Sodium (Na) 1.45%, Calcium (Ca) 1.60%, and Sulfur (S) 0.085%. In addition, increasing the concentration of fly ash has been shown to increase the conductivity of the solution on the insulator surface and reduce the breakdown voltage, with the fastest breakdown voltage value being 38.45 kV and the leakage current reaching 0.318 mA on the wet polluted insulator surface. Abstrak Penurunan kinerja isolator akibat polusi lingkungan, khususnya oleh fly ash yang dihasilkan dari Pembangkit Listrik Tenaga Uap (PLTU). Fly ash mengandung unsur-unsur konduktif yang berpotensi menurunkan resistivitas permukaan isolator, sehingga dapat mempercepat kegagalan isolasi, terutama dalam kondisi lembap atau basah. Oleh karena itu, penting untuk mengkaji secara mendalam pengaruh fly ash terhadap parameter kelistrikan isolator, seperti konduktivitas permukaan dan tegangan tembus. Tujuan utama dari penelitian ini adalah untuk mengetahui seberapa besar dampak kandungan unsur konduktif fly ash terhadap penurunan resistivitas permukaan isolator. Metode yang digunakan meliputi analisis unsur kimia fly ash, simulasi variasi konsentrasi larutan polutan, serta pengujian arus bocor dan tegangan tembus pada laboratorium tegangan tinggi AC. Hasil penelitian menunjukkan bahwa fly ash dari PLTU Anggrek mengandung unsur konduktif Besi (Fe) sebesar 1,595%, Magnesium (Mg) 0,44%, Natrium (Na) 1,45%, Kalsium (Ca) 1,60%, dan Sulfur (S) 0,085%. Selain itu, peningkatan konsentrasi fly ash terbukti meningkatkan konduktivitas larutan pada permukaan isolator serta menurunkan tegangan tembus, dengan nilai tegangan tembus tercepat sebesar 38,45 kV dan arus bocor mencapai 0,318 mA pada kondisi permukaan isolator yang terpolusi basah